РОЛЬ НОВИХ ЕЛЕКТРОННИХ ЗАСОБІВ У ФОРМУВАННІ ВІЗУАЛЬНИХ КОМУНІКАЦІЙ ВИЩИХ НАВЧАЛЬНИХ ЗАКЛАДІВ УКРАЇНИ - Пантус Ніна Михайлівна; Шапран Еліна Олегівна (World Science, 2019)
The article focuses on the necessity of forming the brand of a higher educational institution (HEI) with the use of more electronic means, while it is substantiated that the main tools of modern promotion are so- called new media and the use of mobile application development platforms, which are becoming increasingly popular due to the development of information of society.